Remodelling without a power stroke. (25th October 2013) - Dutta, Arnob; Workman, Jerry L
Abstract : Although chromatin remodellers are thought to exert power strokes to move nucleosomes along DNA, two studies in this issue show that a power stroke is not required for efficient remodelling, indicating that the DNA binding domain primarily tethers remodellers to nucleosomes.